2020
DOI: 10.7759/cureus.6753
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Beware, Giant Ovarian Cysts are Elusive and Rare

Abstract: Giant ovarian cysts, which are described in the literature as measuring more than 10 cms in size in their largest diameter, are rare in occurrence. With the availability of multiple imaging modalities and routine physical examinations, it has become even rarer to find such cases. Ovarian serous cystadenomas, which are benign tumors arising from the ovarian epithelium, represent the most common type. We present a case of a 58-year-old female who came to establish primary care in our clinic. She reported ongoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Routine physical examinations and imaging have enabled clinicians to diagnose ovarian cysts at a relatively smaller size. 1,2 Giant ovarian cysts, which are generally described as more than 10 centimeters in size in their largest diameter and are rare in occurrence. 1,3 This case report emphasizes that cystic ovarian tumors could present masquerading as an ascites.…”
Section: Case Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Routine physical examinations and imaging have enabled clinicians to diagnose ovarian cysts at a relatively smaller size. 1,2 Giant ovarian cysts, which are generally described as more than 10 centimeters in size in their largest diameter and are rare in occurrence. 1,3 This case report emphasizes that cystic ovarian tumors could present masquerading as an ascites.…”
Section: Case Descriptionmentioning
confidence: 99%
“…1,2 Giant ovarian cysts, which are generally described as more than 10 centimeters in size in their largest diameter and are rare in occurrence. 1,3 This case report emphasizes that cystic ovarian tumors could present masquerading as an ascites.…”
Section: Case Descriptionmentioning
confidence: 99%
“…5 At present, there is no uniform definition standard for giant ovarian mass, but most scholars adopt the cutoff of 10 cm in diameter. 6 Previous evidence has indicated that the diameter of ovarian masses is associated with the degree of malignancy, 7 with a diameter exceeding 10 cm suggesting a high incidence of malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with ovarian cancer tend to be at the middle or advanced stage when definitely diagnosed, and some of them even lost the opportunities for surgery (1). Ovarian cancer, the most common gynaecological malignancy, is characterized by an insidious onset, inconspicuous early symptoms, challenging diagnosis, and a poor prognosis, so it has a high fatality rate (2).…”
Section: Introductionmentioning
confidence: 99%